Soft rocks, hard rocks: the world's resources and reserves of Ti and Zr and associated critical minerals. Issue 7 (12th April 2022) - Perks, Cameron; Mudd, Gavin
ABSTRACT: Titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), garnet, and rare earth elements (REO) and their associated minerals are essential for modern society. Despite this, comprehensive public understanding of Ti and Zr resources and reserves (including garnet, Hf contained in zircon, V in titanomagnetite, and REO contained in co/by-product monazite) has been limited.This has led to uncertainty over the possibility of supply shortages in these minerals and has also led to confusion over which Ti and Zr minerals may be in short supply. Addressing this, we compile an extensive database of the world's known Ti and Zr mineral deposits including ore grades, co-products, mineral quality, and geological settings. Our data indicate that 327 mineral deposits in 25 countries contain a collective 2, 648 Mt TiO2 in ilmenite, rutile and leucoxene, 155 Mt of Zr minerals, 23.5 Mt of V, 16.2 Mt of REO and 17.5 Mt of garnet. Just 31% of TiO2 exists within traditional sedimentary deposits (placer and palaeo-placer deposits, but here referred to as sedimentary), with the remainder contained within igneous (54%), metamorphic (1%), and laterite deposits (14%). For igneous TiO2, 58% is contained within ilmenite, 42% in titanomagnetite, and <1% in rutile. 93% of total zirconium minerals are contained in sedimentary deposits. Forward modelling presented in this paper indicates that Ti and Zr resources and reserves are sufficient to meet global demand for several decades. Overall, this unique study presents extensive data on Zr, Ti, Hf, V, garnet and REO resources, makes comments on the future availability of these elements and will therefore be a practical resource for researchers, policymakers, and investors alike.